2021
DOI: 10.3390/molecules26051491
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Energy Storage and Heat Transfer of Nano-Enhanced Phase Change Material (NePCM) in a Shell and Tube Thermal Energy Storage (TES) Unit with a Partial Layer of Eccentric Copper Foam

Abstract: Thermal energy storage units conventionally have the drawback of slow charging response. Thus, heat transfer enhancement techniques are required to reduce charging time. Using nanoadditives is a promising approach to enhance the heat transfer and energy storage response time of materials that store heat by undergoing a reversible phase change, so-called phase change materials. In the present study, a combination of such materials enhanced with the addition of nanometer-scale graphene oxide particles (called na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…However, their study focused primarily on the position of the heat source, leaving room for additional research into the influence of temperature variations on the thermal performance of NEPCM in an enclosure. Similarly, Ghalambaz et al [11] investigated the thermal energy storage and heat transfer of NEPCM in a shell-and-tube thermal energy storage unit, taking into account a partial layer of eccentric copper foam. The findings of this study highlighted the significant impact of temperature on the thermal properties of NEPCM and emphasized the need for further research into the effects of temperature variation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, their study focused primarily on the position of the heat source, leaving room for additional research into the influence of temperature variations on the thermal performance of NEPCM in an enclosure. Similarly, Ghalambaz et al [11] investigated the thermal energy storage and heat transfer of NEPCM in a shell-and-tube thermal energy storage unit, taking into account a partial layer of eccentric copper foam. The findings of this study highlighted the significant impact of temperature on the thermal properties of NEPCM and emphasized the need for further research into the effects of temperature variation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results suggested that using nanoparticles accelerated the charging process and that platelet-shaped nanoparticles provide the fastest pace. More recently published papers, those considering using NePCM for enhancing thermal performance of TES units, can be found in [ 40 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they found that copper nanoparticles had more effective performance in raising heat transfer in comparison with graphene oxide particles. 10 Although the PVT-assisted heat pumps have been the center of interest for researchers, there are still many obscure parts to reach an almost ideal and economical system. In the previous studies, many researchers concentrated on covering the thermal or electrical aspects of the system separately by using renewable energies.…”
Section: Introductionmentioning
confidence: 99%